Serial Magnetic Resonance Imaging in Hypoplastic Left Heart Syndrome Gives Valuable Insight Into Ventricular and Vascular Adaptation - Bellsham-Revell, Hannah R. (Elsevier Biomedical, 2013)
OBJECTIVES: This study sought to investigate changes in magnetic resonance imaging (MRI) ventricular volumes and vascular dimensions before hemi-Fontan (HF) and before total cavopulmonary connection (TCPC) in children with hypoplastic left heart syndrome (HLHS). BACKGROUND: The systemic right ventricle (RV) in HLHS is subject to significant changes in volume loading throughout the surgical stages of palliation, particularly after the HF. METHODS: Fifty-eight patients had paired pre-HF and pre-TCPC MRI for assessment of changes of RV volumes, neoaortic flow, and vascular dimensions. RESULTS: Comparison of pre-HF and pre-TCPC MRI results showed a decrease of indexed RV end-diastolic volume and end-systolic volume (98 ml/m(2) to 87 ml/m(2) and 50 ml/m(2) to 36 ml/m(2), respectively) with stroke volume remaining constant (49 ml/m(2) vs. 51 ml/m(2)), leading to an increased RV ejection fraction (51% vs. 59%). These findings persisted after excluding the 3 patients who underwent tricuspid valve repair as part of their HF procedure. Indexed RV end-diastolic volume plotted against neoaortic stroke volume demonstrated a Frank-Starling–like curve that shifted upward after HF. The indexed distal left and right cross-sectional pulmonary artery areas were reduced after HF. CONCLUSIONS: In HLHS, serial MRI shows the adaptation of the systemic RV after HF with volume reduction in the context of a preserved stroke volume and an increased ejection fraction. The staged palliation in HLHS may be a risk factor particularly for reduced left pulmonary artery growth in itself as no factors investigated in this study were found to significantly impact on this.